The Influence of Outdoor Education and Gender on the Development of Social Values - Ma'mun, Amung; Nugraha, Eka; Hakama, Adli; J, Jahidin (JURNAL PENDIDIKAN JASMANI DAN OLAHRAGA, 2018)
This article reveals the differences in the development of social values through outdoor educational activities (OE) equipped with structured and unstructured games by looking at gender factors. OE activities were conducted in Parongpong and Gunung Artapela, West Bandung West Java Indonesia, followed by 32 students divided into two groups. With a simple 2 x 2 factorial design, the first group was given an OE activity equipped with a structured game and a second group of unstructured games, amounting to 16 people per group. Before and after following OE each sample filled out a questionnaire about the development of social values (environmental care, self-control, communication, and cohesiveness). Gain scores are used to test the hypotheses of the questionnaire after and before following the OE through ANOVA and Tukey. The results are: firstly, there is no overall difference in the effect of OE equipped with structured games with unstructured development of social values; Secondly, there is an interplay between the game model in OE with gender so as to give different effects on the development of social values; Thirdly, there is a difference of influence between OE and structured game with unstructured development of social values in the male gender group, OE equipped with better structured game than unstructured game; Fourth, there is a difference in the effect of OE with unstructured game structured to the development of social values in women's gender groups, OE activities with unstructured games better than structured. OE activities require the right type of game according to their gender. Equips OE with structured games suitable for men and unstructured for women.ABSTRAKArtikel ini mengungkapkan perbedaan perkembangan nilai-nilai sosial melalui kegiatan outdoor education (OE) yang dilengkapi dengan permainan yang terstruktur dan tidak terstruktur dengan melihat faktor jenis kelamin. Aktivitas OE dilakukan di Parongpong dan Gunung Artapela, Bandung Barat, Jawa Barat Indonesia, diikuti oleh 32 siswa dibagi menjadi dua kelompok. Dengan desain faktorial 2 x 2, kelompok pertama diberi kegiatan OE yang dilengkapi dengan permainan terstruktur dan kelompok kedua dari permainan yang tidak terstruktur, yang berjumlah 16 orang per kelompok. Sebelum dan sesudah mengikuti OE setiap sampel mengisi kuesioner tentang pengembangan nilai sosial (perawatan lingkungan, pengendalian diri, komunikasi, dan integitas). Skor gain digunakan untuk menguji hipotesis kuesioner setelah dan sebelum mengikuti OE menggunakan ANOVA dan Tukey. Hasilnya adalah: pertama, tidak ada perbedaan menyeluruhÂ  pengaruh OE yang dilengkapi dengan permainan terstruktur dengan pengembangan nilai-nilai sosial yang tidak terstruktur; Kedua, ada interaksi antara model permainan di OE dengan gender sehingga memberikan efek yang berbeda pada pengembangan nilai-nilai sosial; Ketiga, ada perbedaan pengaruh antara OE dan permainan terstruktur dengan pengembangan nilai-nilai sosial yang tidak terstruktur dalam kelompok gender laki-laki, OE dengan permainan terstrukturÂ  lebih baik daripada permainan yang tidak terstruktur; Keempat, ada perbedaan dalam efek OE dengan permainan terstruktur tidak terstruktur untuk pengembangan nilai-nilai sosial dalam kelompok-kelompok gender perempuan, kegiatan OE dengan permainan yang tidak terstruktur lebih baik daripada yang terstruktur. Kegiatan OE membutuhkan jenis permainan yang tepat sesuai dengan gender mereka. OE dengan permainan terstruktur lebih cocok untuk pria dan tidak terstruktur untuk wanita.